2018
DOI: 10.1021/jacs.7b12815
|View full text |Cite
|
Sign up to set email alerts
|

Electron Accumulative Molecules

Abstract: With the goal to produce molecules with high electron accepting capacity and low reorganization energy upon gaining one or more electrons, a synthesis procedure leading to the formation of a B-N(aromatic) bond in a cluster has been developed. The research was focused on the development of a molecular structure able to accept and release a specific number of electrons without decomposing or change in its structural arrangement. The synthetic procedure consists of a parallel decomposition reaction to generate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 63 publications
0
29
0
1
Order By: Relevance
“…However, (Bmes 2 ) 4 -Per shows stability towards very high reduction potentials with the advantage that it has a high electron capacity, as up to four electrons can be stored. This intriguing property is interesting for applications including molecular switches, 161,162 receptors, 162,163 photoactive dyads 164 or photocatalysis. 143,165 The donor-substituted counterpart, (DPA) 4 -Per, can be oxidized up to ve times according to cyclic voltammetry studies a Excited at the respective l abs (max) of S 1 ) S 0 .…”
Section: Electrochemistrymentioning
confidence: 99%
“…However, (Bmes 2 ) 4 -Per shows stability towards very high reduction potentials with the advantage that it has a high electron capacity, as up to four electrons can be stored. This intriguing property is interesting for applications including molecular switches, 161,162 receptors, 162,163 photoactive dyads 164 or photocatalysis. 143,165 The donor-substituted counterpart, (DPA) 4 -Per, can be oxidized up to ve times according to cyclic voltammetry studies a Excited at the respective l abs (max) of S 1 ) S 0 .…”
Section: Electrochemistrymentioning
confidence: 99%
“…[1][2][3][4][5] Among the various derivatives of carboranes, special attention is paid to p-complexes of transition metals with carborane ligands, called metallacarboranes. The most known of them, cobalt bis(dicarbollide) [3,3 0 -Co(1,2-C 2 B 9 H 11 ) 2 ] À attracts increasing interest from researchers working in various elds from medical chemistry to [6][7][8][9][10][11] materials science [12][13][14][15][16][17][18] to due to its extraordinary high stability, low toxicity 19 and almost unlimited possibilities for chemical modication. 20,21 Recently, we suggested that cobalt bis(dicarbollide) can be used as a structural element in the design of molecular switches.…”
Section: Introductionmentioning
confidence: 99%
“…A more complex behavior was encountered for the cathodic region, where reversible waves were detected for the consecutive, two‐step reduction of the PDI unit to its dianion ( E 1/2 ∼−0.60 and −0.80 V (vs. SCE)), and for the Co III →Co II reduction of the COSAN metal cluster ( E 1/2 ∼−1.47 V (vs. SCE)). Notably, minor differences were observed for the redox signals registered for 1 and 2 concerning reference compounds 3 and 7 , which further evidence that the COSAN and PDI moieties are not electronically coupled in the conjugates [30] …”
Section: Resultsmentioning
confidence: 79%